Preparation process of two-chamber bipolar membrane based on bipolar membrane and anion exchange membrane
By spraying nano titanium oxide sol on the surface of the bipolar film to form an anti-pollution coating and photocatalyzed organic matter, the problems of traditional bipolar films being susceptible to contamination and poor operating stability are solved, and the performance and service life of the film are significantly improved. It is suitable for treating industrial liquids containing trace organic matter.
Patent Information
- Application Number
- CN202510318708.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional bipolar membrane technology is blocked due to the easy adsorption of organic matter on the membrane surface, and requires frequent shutdown and strict water quality requirements, which limits the application of industrial material and liquid containing trace pollutants. At the same time, problems such as weak interface bonding force of membrane modules and rough packaging process lead to poor operating stability, which restricts large-scale production efficiency.
The surface of the bipolar film is sprayed with nanotitanium oxide sol to form an anti-pollution coating, which enhances the ion selective permeability and chemical corrosion resistance of the film, and decomposes organic pollutants through photocatalytic action. At the same time, the membrane stack packaging parameters and fluid precharge design are refined to eliminate the risks of failure such as abnormal interface contact resistance and residual runner bubbles.
It significantly improves the comprehensive performance of the two-chamber bipolar membrane system, extends the service life of the membrane stack, reduces the frequency of chemical cleaning, enhances the mechanical stability of the membrane, and breaks through the strict restrictions on the quality of water inlet. It is suitable for industrial liquid treatment scenarios containing trace organic matter.
Smart Images

Figure CN119869238A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bipolar membranes, and in particular relates to a preparation process of a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane. Background Art
[0002] The two-chamber bipolar membrane is a membrane separation device composed of anion and cation exchange membranes and has bipolar conductive properties. It is mainly composed of a cation exchange layer, anion exchange layer and an intermediate interface layer. During operation, the two-chamber bipolar membrane passes through an electrolyte solution and applies voltage to the anode and cathode, so that cations and anions pass through the anion and cation exchange membranes respectively, thereby achieving solution separation and concentration. The membrane is widely used in acid and alkali preparation, wastewater treatment, food processing and other fields. The two-chamber bipolar membrane has the advantages of simple operation, low energy consumption and environmental friendliness, but its performance is affected by factors such as membrane materials and operating conditions. With technological advances, the two-chamber bipolar membrane has achieved remarkable results in improving membrane performance and reducing costs, and has broad market prospects.
[0003] However, traditional bipolar membrane technology is prone to organic matter adsorption on the membrane surface, which leads to ion channel blockage. It requires frequent shutdowns for cleaning and has strict requirements on the inlet water quality, which limits its application in treating industrial liquids containing trace pollutants. At the same time, problems such as weak interface bonding of membrane components and rough packaging process lead to poor operating stability. Mechanical damage and efficiency attenuation are prone to occur under high current density, which restricts the efficiency of large-scale production. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a preparation process of a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane, the process comprising the following steps:
[0006] S1: Prepare a bipolar membrane and anion exchange membrane assembly, align the bipolar membrane and the anion exchange membrane in order, ensure that the cation surface of the bipolar membrane faces the anion exchange membrane, and form a composite membrane structure.
[0007] S2: Install the composite membrane assembly between the nickel electrode plates and tighten them symmetrically and evenly with hexagonal bolts to ensure that the membrane surface fits tightly with the electrode plates and no bubbles remain.
[0008] S3: The surface of the composite membrane is sprayed with nano-titanium oxide sol to form an anti-pollution coating, which is cured at 60°C for 30 minutes after spraying to enhance the membrane's ion selective permeability and chemical corrosion resistance.
[0009] S4: Prepare the electrode liquid as 3wt% sulfuric acid solution and inject it into the E liquid tank; inject the salt solution as the treated liquid into the S liquid tank; inject the acid solution into the B liquid tank, and ensure that the temperature of the solution in each liquid tank is controlled at 25-30℃.
[0010] S5: Connect the hose to the water inlet pipes E, S, and B, immerse the water outlet pipes in the corresponding liquid tanks, turn on the external power supply and pump power supply, start the automatic suction system of the ear cleaning bulb, and complete the pipeline pre-filling operation.
[0011] S6: Select the two-chamber bipolar membrane mode in the operation interface, set the output voltage to 25V and the current to 4.4A, turn on the material pump, acid-base pump and polar water pump, and observe the water output status of each chamber until it stabilizes.
[0012] S7: Start the power supply, monitor the voltage, current and conductivity curves in real time, synchronize them to the mobile phone through the Internet of Things function, and dynamically adjust the cooling system to maintain the solution temperature below 35°C.
[0013] S8: After the experiment, turn off the power and stop the pump, and use the pneumatic purge device to automatically remove the residual liquid in the membrane stack and pipeline to avoid manual operation errors.
[0014] S9: Collect the product and clean the membrane stack, use pure water circulation and 1% hydrochloric acid to clean it in turn, and finally immerse the membrane stack in a protective solution containing nano silver ions and seal it for storage to inhibit the growth of microorganisms.
[0015] In a preferred embodiment, in step S1, the cation exchange layer of the bipolar membrane is strictly aligned with the active surface of the anion exchange membrane, and an optical aligner is used to assist in calibration to ensure that the edge deviation of the two membranes is less than 0.5 mm. Assembly must be performed in a dust-free environment with a humidity of 80%, and the contact surface of the membrane is pre-sprayed with 0.1 mol / L sodium chloride wetting solution to eliminate interface bubbles. A uniform pressure of 0.1 MPa is applied between the composite membrane layers for 10 minutes to promote the ion exchange groups to form a molecular-level chimeric structure. Finally, a standard component with a total thickness of 1.2 mm and an effective membrane area of 75 mm×195 mm is formed.
[0016] In a preferred embodiment, in step S2, a nickel electrode plate with a surface roughness of Ra≤0.8μm is selected, and the oxide layer is removed by ultrasonic cleaning with a 5% citric acid solution for 15 minutes before installation. The composite membrane assembly is placed between two electrode plates and tightened with hexagonal bolts in three gradient steps in diagonal order: the first pre-tightening is to 2N·m, the second increase is to 5N·m, and the final torque is locked to 8N·m. The resistance value of the membrane stack is monitored in real time during the packaging process to ensure that the contact resistance is stable within the range of 0.5Ω±0.1Ω. After packaging, deionized water is injected into the membrane stack flow channel to verify that the sealing reaches 0.3MPa without leakage.
[0017] In a preferred embodiment, in step S3, the specific method includes the following steps:
[0018] Sol preparation: nano titanium oxide powder and deionized water are mixed at a mass ratio of 1:50, 0.5% polyethylene glycol dispersant is added, and an ultrasonic oscillator is used to disperse at a frequency of 40 kHz for 30 minutes to form a uniform and stable nano sol suspension.
[0019] Pretreatment activation: immerse the composite membrane assembly in a 5wt% sodium hydroxide solution for 10 minutes, take it out and rinse it with pure water until it is neutral, and dry it in a 50°C oven for 20 minutes to enhance the binding force between the active groups on the membrane surface and the nanoparticles.
[0020] High-pressure spraying: Use a high-pressure spray gun to spray the composite film surface back and forth at a vertical distance of 20 cm at a pressure of 0.3 MPa. The thickness of a single coating is controlled at 2-3 μm. Spray 3 times in total, with an interval of 5 minutes each time for natural leveling.
[0021] Curing treatment: Place the sprayed membrane assembly in a 60°C constant temperature drying oven for 30 minutes to allow the nano-titanium oxide particles to form a chemical bond with the membrane surface, and then activate the photocatalytic performance under ultraviolet light.
[0022] Performance enhancement: the nano-titanium oxide coating decomposes organic pollutants through photocatalysis, while its super hydrophilicity reduces the adhesion rate of pollutants on the membrane surface.
[0023] In a preferred embodiment, in step S4, 800 mL of 3wt% sulfuric acid solution is injected into the electrode liquid E tank, and the conductivity is maintained at 45-50 mS / cm; 1000 mL of 1 mol / L sodium sulfate salt solution is loaded into the treated liquid S tank; 500 mL of 0.5 mol / L dilute sulfuric acid is pre-set in the acid liquid B tank. The liquid temperature of the three tanks is synchronously controlled at 28°C ± 1°C using a constant temperature water bath system, and real-time feedback adjustment is performed through a PT100 temperature sensor. The solution preparation is carried out under nitrogen protection throughout the process, and the dissolved oxygen content is controlled below 0.5 mg / L to avoid electrode oxidation.
[0024] In a preferred embodiment, in step S5, the Φ6mm fluororubber hose is connected to the E, S, and B liquid tanks to the corresponding inlets, and the pipeline is pre-filled with a fully automatic arterial flow generator: first, 50kPa negative pressure is sucked for 30 seconds to remove the pipeline bubbles, and then switched to a 10Hz pulsating flow mode for 3 minutes. The system monitors the transparency of the liquid through an online turbidity sensor, and the filling is determined to be complete when the transmittance is ≥95%. The pre-filling process simultaneously activates the membrane stack wetting state detection function to ensure that the moisture content of the membrane surface is above 98%.
[0025] In a preferred embodiment, in step S6, after selecting the two-chamber bipolar membrane mode on the touch screen, set the constant voltage to 25V and the current limit to 4.4A, and start the parameter self-test function to verify that the membrane stack withstands voltage>30V and the short-circuit current>6A. The material pump and the acid-base pump are started at a nominal flow rate of 300mL / min, and the polar water pump is set to a flushing flow rate of 200mL / min. The water jet morphology of each chamber is captured in real time by a high-frame-rate industrial camera. When it is observed that the S slot outlet forms a continuous laminar flow and the B slot produces a periodic vortex flow state, the fluid distribution is determined to be up to standard.
[0026] In a preferred embodiment, in step S7, the system automatically switches to constant voltage mode after the power is started, and the current density data is collected every 5 seconds through the Hall sensor. When the current fluctuation exceeds ±0.2A, PID adjustment is triggered. The Internet of Things module uploads voltage, conductivity, and temperature data to the cloud every 30 seconds, and the mobile phone can remotely set the temperature control strategy: when the S tank liquid temperature reaches 34°C, the built-in semiconductor refrigeration chip is started to maintain the solution temperature difference ≤2°C. The efficiency of the photocatalytic coating is monitored online by a UV irradiance meter to ensure that the light intensity at a wavelength of 365nm is ≥10mW / cm 2 .
[0027] In a preferred embodiment, in step S8, after clicking the stop button, the system executes a three-level shutdown procedure: first, the power is cut off within 0.5 seconds and the brake resistor is started to consume the residual power; then the pneumatic purge system uses 0.25MPa clean nitrogen to pulse purge the membrane stack flow channel for 20 seconds, and the removal rate is greater than 99.8%; finally, the membrane stack is automatically injected with a buffer protection liquid with a pH of 6.8 to form a 3mm thick liquid film to prevent drying. The whole process pressure sensor ensures that the membrane stack withstands a pressure difference of ≤0.05MPa to avoid mechanical damage.
[0028] In a preferred embodiment, in step S9, the polytetrafluoroethylene discharge valve at the bottom of the S tank is opened, and the product solution is accurately measured by a mass flow meter, with the error controlled within ±1%. The membrane stack is cleaned in a three-stage procedure: first, 40°C ultrapure water is used for 15 minutes at a flow rate of 500 mL / min; then, a 1% hydrochloric acid solution is switched at 0.2 A / cm 2 Electrochemical cleaning was performed for 8 minutes at a current density; finally, the membrane stack was statically soaked in a preservation solution containing 50ppm nano silver ions for 24 hours. The maintained membrane stack was packaged in an inert gas environment with a humidity of 95%, and the shelf life was extended to 180 days.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] 1. In the present invention, the nano-titanium oxide sol anti-pollution coating technology is introduced to significantly improve the comprehensive performance of the two-chamber bipolar membrane system. Traditional bipolar membranes are susceptible to adsorption of pollutants during the separation of organic matter, resulting in blockage of ion channels on the membrane surface and attenuation of electrochemical efficiency. This process constructs a photocatalytic active layer on the membrane surface, which can continuously decompose residual organic matter under ultraviolet light. At the same time, it reduces the probability of pollutant adhesion through super-hydrophilic properties, so that the membrane component maintains stable ion selective permeability during long-term operation, effectively extending the service life of the membrane stack and reducing the frequency of chemical cleaning. In addition, the chemical bonding between the nano-coating and the membrane substrate strengthens the interfacial bonding force, avoids the problem of easy shedding of traditional physical coating, and ensures the mechanical stability of the membrane stack under high current density.
[0031] 2. In the present invention, the introduction of nano-coating enables the membrane assembly to withstand more complex solution environments, and is particularly suitable for industrial liquid treatment scenarios containing trace organic matter, breaking through the strict restrictions of traditional bipolar membranes on the quality of influent water. The refined control of membrane stack packaging parameters and the intelligent design of fluid pre-filling in the process eliminate the common fault risks such as abnormal interface contact resistance and residual bubbles in the flow channel. The entire system greatly improves the acid-base conversion efficiency through the dynamic regulation of the Internet of Things and the synergistic effect of photocatalysis, while reducing energy consumption and operation and maintenance costs, providing a reliable solution for the large-scale application of industrial-grade bipolar membrane electrodialysis technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Reference Figure 1 ,
[0035] A preparation process of a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane, the process comprising the following steps:
[0036] S1: Prepare a bipolar membrane and anion exchange membrane assembly, align the bipolar membrane and the anion exchange membrane in order, ensure that the cation surface of the bipolar membrane faces the anion exchange membrane, and form a composite membrane structure.
[0037] S2: Install the composite membrane assembly between the nickel electrode plates and tighten them symmetrically and evenly with hexagonal bolts to ensure that the membrane surface fits tightly with the electrode plates and no bubbles remain.
[0038] S3: The surface of the composite membrane is sprayed with nano-titanium oxide sol to form an anti-pollution coating, which is cured at 60°C for 30 minutes after spraying to enhance the membrane's ion selective permeability and chemical corrosion resistance.
[0039] S4: Prepare the electrode liquid as 3wt% sulfuric acid solution and inject it into the E liquid tank; inject the salt solution as the treated liquid into the S liquid tank; inject the acid solution into the B liquid tank, and ensure that the temperature of the solution in each liquid tank is controlled at 25-30℃.
[0040] S5: Connect the hose to the water inlet pipes E, S, and B, immerse the water outlet pipes in the corresponding liquid tanks, turn on the external power supply and pump power supply, start the automatic suction system of the ear cleaning bulb, and complete the pipeline pre-filling operation.
[0041] S6: Select the two-chamber bipolar membrane mode in the operation interface, set the output voltage to 25V and the current to 4.4A, turn on the material pump, acid-base pump and polar water pump, and observe the water output status of each chamber until it stabilizes.
[0042] S7: Start the power supply, monitor the voltage, current and conductivity curves in real time, synchronize them to the mobile phone through the Internet of Things function, and dynamically adjust the cooling system to maintain the solution temperature below 35°C.
[0043] S8: After the experiment, turn off the power and stop the pump, and use the pneumatic purge device to automatically remove the residual liquid in the membrane stack and pipeline to avoid manual operation errors.
[0044] S9: Collect the product and clean the membrane stack, use pure water circulation and 1% hydrochloric acid to clean it in turn, and finally immerse the membrane stack in a protective solution containing nano silver ions and seal it for storage to inhibit the growth of microorganisms.
[0045] In step S1, the cation exchange layer of the bipolar membrane is strictly aligned with the active surface of the anion exchange membrane, and an optical aligner is used to assist in calibration to ensure that the edge deviation of the two membranes is less than 0.5mm. Assembly must be carried out in a dust-free environment with a humidity of 80%, and the contact surface of the membrane is pre-sprayed with 0.1mol / L sodium chloride wetting solution to eliminate interface bubbles. A uniform pressure of 0.1MPa is applied between the composite membrane layers for 10 minutes to promote the formation of a molecular-level chimeric structure by the ion exchange groups. Finally, a standard component with a total thickness of 1.2mm and an effective membrane area of 75mm×195mm is formed.
[0046] In step S2, a nickel electrode plate with a surface roughness of Ra≤0.8μm is selected, and the oxide layer is removed by ultrasonic cleaning with a 5% citric acid solution for 15 minutes before installation. The composite membrane assembly is placed between two electrode plates and tightened three times in a diagonal order using hexagonal bolts: the first pre-tightening is to 2N·m, the second increase is to 5N·m, and the final torque is locked to 8N·m. The resistance value of the membrane stack is monitored in real time during the packaging process to ensure that the contact resistance is stable within the range of 0.5Ω±0.1Ω. After packaging, deionized water is injected into the membrane stack flow channel to verify that the sealing reaches 0.3MPa without leakage.
[0047] In step S3, the specific method includes the following steps:
[0048] Sol preparation: nano titanium oxide powder and deionized water are mixed at a mass ratio of 1:50, 0.5% polyethylene glycol dispersant is added, and an ultrasonic oscillator is used to disperse at a frequency of 40 kHz for 30 minutes to form a uniform and stable nano sol suspension.
[0049] Pretreatment activation: immerse the composite membrane assembly in a 5wt% sodium hydroxide solution for 10 minutes, take it out and rinse it with pure water until it is neutral, and dry it in a 50°C oven for 20 minutes to enhance the binding force between the active groups on the membrane surface and the nanoparticles.
[0050] High-pressure spraying: Use a high-pressure spray gun to spray the composite film surface back and forth at a vertical distance of 20 cm at a pressure of 0.3 MPa. The thickness of a single coating is controlled at 2-3 μm. Spray 3 times in total, with an interval of 5 minutes each time for natural leveling.
[0051] Curing treatment: Place the sprayed membrane assembly in a 60°C constant temperature drying oven for 30 minutes to allow the nano-titanium oxide particles to form a chemical bond with the membrane surface, and then activate the photocatalytic performance under ultraviolet light.
[0052] Performance enhancement: the nano-titanium oxide coating decomposes organic pollutants through photocatalysis, while its super hydrophilicity reduces the adhesion rate of pollutants on the membrane surface.
[0053] In step S4, 800 mL of 3 wt% sulfuric acid solution is injected into the electrode liquid E tank, and the conductivity is maintained at 45-50 mS / cm; 1000 mL of 1 mol / L sodium sulfate salt solution is loaded into the treated liquid S tank; 500 mL of 0.5 mol / L dilute sulfuric acid is pre-set in the acid liquid B tank. The liquid temperature of the three tanks is synchronously controlled at 28°C ± 1°C using a constant temperature water bath system, and real-time feedback adjustment is performed through a PT100 temperature sensor. The solution preparation is carried out under nitrogen protection throughout the process, and the dissolved oxygen content is controlled below 0.5 mg / L to avoid electrode oxidation.
[0054] In step S5, the Φ6mm fluororubber hose is connected to the E, S, and B liquid tanks to the corresponding inlets respectively, and the pipeline is pre-filled with a fully automatic arterial flow generator: first, 50kPa negative pressure is sucked for 30 seconds to remove the bubbles in the pipeline, and then switched to a 10Hz pulsating flow mode for 3 minutes. The system monitors the transparency of the liquid through an online turbidity sensor, and determines that the filling is complete when the transmittance is ≥95%. The membrane stack wetting state detection function is simultaneously activated during the pre-filling process to ensure that the moisture content of the membrane surface is above 98%.
[0055] In step S6, after selecting the two-chamber bipolar membrane mode on the touch screen, set the constant voltage to 25V and the current limit to 4.4A, and start the parameter self-test function to verify that the membrane stack withstands voltage > 30V and the short-circuit current > 6A. The material pump and acid-base pump are started at a nominal flow rate of 300mL / min, and the polar water pump is set to a flushing flow rate of 200mL / min. The high-frame-rate industrial camera is used to capture the jet morphology of each chamber in real time. When it is observed that the S slot outlet forms a continuous laminar flow and the B slot produces a periodic vortex flow state, the fluid distribution is determined to be up to standard.
[0056] In step S7, after the power is turned on, the system automatically switches to the constant voltage mode, and the current density data is collected every 5 seconds through the Hall sensor. When the current fluctuation exceeds ±0.2A, the PID adjustment is triggered. The IoT module uploads the voltage, conductivity, and temperature data to the cloud every 30 seconds, and the mobile phone can remotely set the temperature control strategy: when the S tank liquid temperature reaches 34°C, the built-in semiconductor refrigeration chip is started to maintain the solution temperature difference ≤2°C. The efficiency of the photocatalytic coating is monitored online by a UV irradiance meter to ensure that the light intensity at a wavelength of 365nm is ≥10mW / cm 2 .
[0057] In step S8, after clicking the stop button, the system executes a three-level shutdown procedure: first, the power is cut off within 0.5 seconds and the brake resistor is started to consume the residual power; then the pneumatic purge system uses 0.25MPa clean nitrogen to pulse purge the membrane stack flow channel for 20 seconds, with a removal rate of >99.8%; finally, the membrane stack is automatically injected with a buffer protection liquid with a pH of 6.8 to form a 3mm thick liquid film to prevent drying. The pressure sensor during the whole process ensures that the membrane stack withstands a pressure difference of ≤0.05MPa to avoid mechanical damage.
[0058] In step S9, the polytetrafluoroethylene discharge valve at the bottom of the S tank is opened, and the product solution is accurately measured by a mass flow meter with an error control within ±1%. The membrane stack is cleaned in a three-stage procedure: first, 40°C ultrapure water is used for 15 minutes at a flow rate of 500 mL / min; then, a 1% hydrochloric acid solution is switched at 0.2 A / cm 2 Electrochemical cleaning was performed for 8 minutes at a current density; finally, the membrane stack was statically soaked in a preservation solution containing 50ppm nano silver ions for 24 hours. The maintained membrane stack was packaged in an inert gas environment with a humidity of 95%, and the shelf life was extended to 180 days.
[0059] From the above, it can be known that: In the present invention, the introduction of nano-titanium oxide sol anti-pollution coating technology has significantly improved the comprehensive performance of the two-chamber bipolar membrane system. Traditional bipolar membranes are susceptible to adsorption of pollutants during the separation of organic matter, resulting in blockage of ion channels on the membrane surface and attenuation of electrochemical efficiency. This process constructs a photocatalytic active layer on the membrane surface, which can continuously decompose residual organic matter under ultraviolet light, while reducing the probability of pollutant adhesion through super-hydrophilic properties, so that the membrane component maintains stable ion selective permeability during long-term operation, effectively extending the service life of the membrane stack and reducing the frequency of chemical cleaning. In addition, the chemical bonding between the nano-coating and the membrane substrate strengthens the interfacial bonding force, avoids the problem of easy shedding of traditional physical coatings, and ensures the mechanical stability of the membrane stack under high current density.
[0060] In the present invention, the introduction of nano-coating enables the membrane assembly to withstand more complex solution environments, and is particularly suitable for industrial liquid treatment scenarios containing trace organic matter, breaking through the strict restrictions of traditional bipolar membranes on the quality of influent water. The refined control of membrane stack packaging parameters and the intelligent design of fluid pre-filling in the process eliminate common fault risks such as abnormal interface contact resistance and residual bubbles in the flow channel. The entire system greatly improves the acid-base conversion efficiency through dynamic regulation of the Internet of Things and synergistic effects of photocatalysis, while reducing energy consumption and operation and maintenance costs, providing a reliable solution for the large-scale application of industrial-grade bipolar membrane electrodialysis technology.
[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0062] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane, characterized in that: The process comprises the following steps: S1: preparing a bipolar membrane and anion exchange membrane assembly, aligning the bipolar membrane and the anion exchange membrane in order, ensuring that the cation surface of the bipolar membrane faces the anion exchange membrane, and forming a composite membrane structure; S2: Install the composite membrane assembly between the nickel electrode plates and tighten them symmetrically and evenly with hexagonal bolts to ensure that the membrane surface fits tightly with the electrode plates and no bubbles remain; S3: Spraying the composite membrane surface with nano-titanium oxide sol to form an anti-pollution coating, which is then cured at 60°C for 30 minutes to enhance the membrane's ion selective permeability and chemical corrosion resistance; S4: Prepare an electrode solution of 3wt% sulfuric acid solution and inject it into the E tank; inject the salt solution as the treated liquid into the S tank; inject the acid solution into the B tank, and ensure that the temperature of the solution in each tank is controlled at 25-30°C; S5: Connect the hose to the water inlet pipes E, S, and B, immerse the water outlet pipes in the corresponding liquid tanks, turn on the external power supply and pump power supply, start the automatic suction system of the ear cleaning ball, and complete the pipeline pre-filling operation; S6: Select the two-chamber bipolar membrane mode in the operation interface, set the output voltage to 25V and the current to 4.4A, turn on the material pump, acid-base pump and polar water pump, and observe the water output status of each chamber until it is stable; S7: Start the power supply, monitor the voltage, current and conductivity curve in real time, synchronize them to the mobile phone through the Internet of Things function, and dynamically adjust the cooling system to maintain the solution temperature below 35°C; S8: After the experiment, turn off the power and stop the pump, and use the pneumatic purge device to automatically remove the residual liquid in the membrane stack and pipeline to avoid manual operation errors; S9: Collect the product and clean the membrane stack, use pure water circulation and 1% hydrochloric acid to clean it in turn, and finally immerse the membrane stack in a protective solution containing nano silver ions and seal it for storage to inhibit the growth of microorganisms.
2. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In the step S1, the cation exchange layer of the bipolar membrane is strictly aligned with the active surface of the anion exchange membrane, and an optical aligner is used to assist in calibration to ensure that the edge deviation of the two membranes is less than 0.5 mm; the assembly needs to be operated in a dust-free environment with a humidity of 80%, and the contact surface of the membrane is pre-sprayed with 0.1 mol / L sodium chloride wetting solution to eliminate interface bubbles; a uniform pressure of 0.1 MPa is applied between the composite membrane layers for 10 minutes to promote the ion exchange groups to form a molecular-level chimeric structure; and finally a standard component with a total thickness of 1.2 mm and an effective membrane area of 75 mm×195 mm is formed.
3. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In the step S2, a nickel electrode plate with a surface roughness of Ra≤0.8μm is selected, and the oxide layer is removed by ultrasonic cleaning with a 5% citric acid solution for 15 minutes before installation; the composite membrane assembly is placed between two electrode plates, and is tightened three times in a gradient manner in a diagonal order using hexagonal bolts: the first pre-tightening is to 2N·m, the second is increased to 5N·m, and the final torque is locked to 8N·m; the resistance value of the membrane stack is monitored in real time during the packaging process to ensure that the contact resistance is stable within the range of 0.5Ω±0.1Ω.
4. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In step S3, the specific method includes the following steps: Sol preparation: nano titanium oxide powder and deionized water are mixed at a mass ratio of 1:50, 0.5% polyethylene glycol dispersant is added, and an ultrasonic oscillator is used to disperse at a frequency of 40 kHz for 30 minutes to form a uniform and stable nano sol suspension; Pretreatment activation: immerse the composite membrane assembly in a 5wt% sodium hydroxide solution for 10 minutes, take it out and rinse it with pure water until it is neutral, and dry it in a 50℃ oven for 20 minutes to enhance the binding force between the active groups on the membrane surface and the nanoparticles; High-pressure spraying: Use a high-pressure spray gun to spray the composite film surface back and forth at a vertical distance of 20 cm at a pressure of 0.3 MPa. The thickness of a single coating is controlled at 2-3 μm. Spray 3 times in total, with an interval of 5 minutes each time for natural leveling. Curing treatment: the sprayed membrane assembly is placed in a 60°C constant temperature drying oven for 30 minutes to allow the nano-titanium oxide particles to form a chemical bond with the membrane surface, and then the photocatalytic performance is activated under ultraviolet light; Performance enhancement: the nano-titanium oxide coating decomposes organic pollutants through photocatalysis, while its super hydrophilicity reduces the adhesion rate of pollutants on the membrane surface.
5. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In the step S4, 800 mL of 3 wt% sulfuric acid solution is injected into the electrode liquid E tank, and the conductivity is maintained at 45-50 mS / cm; 1000 mL of 1 mol / L sodium sulfate salt solution is loaded into the treated liquid S tank; 500 mL of 0.5 mol / L dilute sulfuric acid is pre-placed in the acid liquid B tank; the liquid temperatures of the three tanks are synchronously controlled at 28°C±1°C using a constant temperature water bath system, and are adjusted by real-time feedback through a PT100 temperature sensor; the solution preparation is carried out under nitrogen protection throughout the process, and the dissolved oxygen content is controlled below 0.5 mg / L to avoid electrode oxidation.
6. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In step S5, the Φ6mm fluororubber hose is respectively connected to the E, S, and B liquid tanks to the corresponding inlets, and the pipeline is pre-filled with a fully automatic arterial flow generator: first, 50kPa negative pressure is sucked for 30 seconds to remove the bubbles in the pipeline, and then switched to a 10Hz pulsating flow mode for 3 minutes; the system monitors the liquid transparency through an online turbidity sensor, and determines that the filling is complete when the transmittance is ≥95%; the membrane stack wetting state detection function is simultaneously activated during the pre-filling process to ensure that the moisture content of the membrane surface is above 98%.
7. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In the step S6, after selecting the two-chamber bipolar membrane mode on the touch screen, set the constant voltage to 25V and the current limit to 4.4A, start the parameter self-test function to verify that the membrane stack withstand voltage is >30V and the short-circuit current is >6A; the material pump and the acid-base pump are started at a nominal flow rate of 300mL / min, and the polar water pump is set to a flushing flow rate of 200mL / min; the high-frame-rate industrial camera is used to capture the water jet morphology of each chamber in real time, and when it is observed that a continuous laminar flow is formed at the outlet of the S slot and a periodic vortex flow state is generated at the B slot, it is determined that the fluid distribution meets the standard.
8. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In step S7, after the power is turned on, the system automatically switches to the constant voltage mode, and the current density data is collected every 5 seconds through the Hall sensor. When the current fluctuation exceeds ±0.2A, the PID adjustment is triggered; the Internet of Things module uploads the voltage, conductivity, and temperature data to the cloud every 30 seconds, and the mobile phone can remotely set the temperature control strategy: when the S tank liquid temperature reaches 34°C, the built-in semiconductor refrigeration chip is started to maintain the solution temperature difference ≤2°C; the photocatalytic coating efficiency is monitored online by the ultraviolet irradiance meter to ensure that the light intensity at a wavelength of 365nm is ≥10mW / cm 2 .
9. A process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane as claimed in claim 1, characterized in that: In step S8, after clicking the stop button, the system executes a three-level shutdown procedure: first, the power is cut off within 0.5 seconds and the braking resistor is started to consume the residual electrical energy; then the pneumatic purge system performs a 20-second pulse purge on the membrane stack flow channel with 0.25MPa clean nitrogen, and the removal rate is greater than 99.8%; finally, the membrane stack is automatically injected with a buffer protection liquid with a pH of 6.8 to form a 3mm thick liquid film.
10. The process for preparing a two-chamber bipolar membrane based on a bipolar membrane and an anion exchange membrane according to claim 1, characterized in that: In step S9, the polytetrafluoroethylene discharge valve at the bottom of the S tank is opened, and the product solution is accurately measured by a mass flow meter, with the error controlled within ±1%; the membrane stack is cleaned in a three-stage procedure: first, 40°C ultrapure water is used for circulating flushing at a flow rate of 500 mL / min for 15 minutes; then, a 1% hydrochloric acid solution is switched at 0.2 A / cm 2 Electrochemical cleaning was performed at a current density of 8 minutes; finally, static immersion was performed in a preservation solution containing 50 ppm nano silver ions for 24 hours.
Citation Information
Cited By
Uninterruptible power supply and distribution system special for bipolar membrane system
CN120810905A